2022
DOI: 10.1155/2022/8086991
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hub Genes Associated with Immune Infiltration in Cardioembolic Stroke by Whole Blood Transcriptome Analysis

Abstract: Cardioembolic stroke (CS) is the most common type of ischemic stroke in the clinic, leading to high morbidity and mortality worldwide. Although many studies have been conducted, the molecular mechanism underlying CS has not been fully grasped. This study was aimed at exploring the molecular mechanism of CS using comprehensive bioinformatics analysis and providing new insights into the pathophysiology of CS. We downloaded the public datasets GSE58294 and GSE16561. Differentially expressed genes (DEGs) were scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…We also discovered 3 SNPs each known to code the ATG16L1 and THADA genes in chromosome 2, IKZF3 and PGAP3 genes in chromosome 17, DOCK8 gene in chromosome 9, TSPAN14 gene in chromosome 10 and ETS1 gene in chromosome 11. FAM53B is known to be associated with humoral immune reponse, regulation of immune effector process, and regulation of lymphocyte activation [ 57 ]; reduced expression of PGAP3 is known to be related to impaired clearance of apoptotic cells and has been observed in CD and UC patients [ 44 ]; TSPAN14 is expressed in immune cell types participating in immunity and inflammation, and is positively correlated with microphages and neutrophils and negatively correlated with T cells CD8 [ 58 ]; and finally, ETS1 is known to be over-expressed in intestinal epithelial cells of patients with UC [ 59 ], and has also been linked to fistula formation, an epithelial defect caused by destructive inflammation, in the pathogenesis of CD [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…We also discovered 3 SNPs each known to code the ATG16L1 and THADA genes in chromosome 2, IKZF3 and PGAP3 genes in chromosome 17, DOCK8 gene in chromosome 9, TSPAN14 gene in chromosome 10 and ETS1 gene in chromosome 11. FAM53B is known to be associated with humoral immune reponse, regulation of immune effector process, and regulation of lymphocyte activation [ 57 ]; reduced expression of PGAP3 is known to be related to impaired clearance of apoptotic cells and has been observed in CD and UC patients [ 44 ]; TSPAN14 is expressed in immune cell types participating in immunity and inflammation, and is positively correlated with microphages and neutrophils and negatively correlated with T cells CD8 [ 58 ]; and finally, ETS1 is known to be over-expressed in intestinal epithelial cells of patients with UC [ 59 ], and has also been linked to fistula formation, an epithelial defect caused by destructive inflammation, in the pathogenesis of CD [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…CLEC4D is one of the hub genes that is differentially expressed between IS patients and controls 21 and may be involved in mir-27a-3p−CLEC4D regulation. 22 In addition, it was previously found that CLEC4D and CD163 are immune biomarkers for IS, and these genes were used to construct classification models based on a neural network algorithm.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Enrichment of a wide host of functions including leukocyte activation, filopodium assembly, cytoskeleton organization, regulation of cellular response to transforming growth factor beta receptor, and gene silencing point to the breadth of cell types in blood undergoing cell proliferation, activation, and migration in the first 72 h after ischemic stroke. Through different approaches, Li et al [ 89 ] identified several stroke-related hub genes, where one of them is common to our analysis in whole blood hub genes ( TSPAN14 ). This gene is involved in the regulation of Notch signaling pathway [ 90 ] and may be a promising target in CE stroke.…”
Section: Discussionmentioning
confidence: 99%